2007
DOI: 10.1007/s00216-007-1548-9
|View full text |Cite
|
Sign up to set email alerts
|

pH-sensitive holograms for continuous monitoring in plasma

Abstract: Conventional electrochemical methods of determining the pH of body fluids have drawbacks. Newer optical methods offer the promise of miniaturisation and continuous in vivo measurements without drift. This report examines the ability of a holographic sensor based on a thin-film, biocompatible hydrogel (approximately 10 microm) of poly(2-hydroxyethyl methacrylate) and ionisable 2-(dimethylaminoethyl) methacrylate to accurately measure the pH of blood plasma ex vivo. It is found that the sensors behave in a fully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Newer optical methods offer the promise of miniaturisation and continuous in vivo measurements without drift. The ability of a holographic sensor based on a thin-film, biocompatible hydrogel (approximately 10 μm) of poly(2-hydroxyethyl methacrylate) and ionisable 2-(dimethylaminoethyl) methacrylate to accurately measure the pH of blood plasma ex vivo was investigated in [62]. It was found that the sensors behave in a fully reversible manner.…”
Section: Polymers and Methods Used For Ph Measurementsmentioning
confidence: 99%
“…Newer optical methods offer the promise of miniaturisation and continuous in vivo measurements without drift. The ability of a holographic sensor based on a thin-film, biocompatible hydrogel (approximately 10 μm) of poly(2-hydroxyethyl methacrylate) and ionisable 2-(dimethylaminoethyl) methacrylate to accurately measure the pH of blood plasma ex vivo was investigated in [62]. It was found that the sensors behave in a fully reversible manner.…”
Section: Polymers and Methods Used For Ph Measurementsmentioning
confidence: 99%
“…Optical pH sensing implemented with fiber optics [ 6 , 7 , 8 , 9 ] has been previously investigated as an alternative to a glass electrode for biomedical measurements because it combines small size and calibration stability. A pH indicator is immobilized at the distal end of an optical fiber by adsorption, covalent bonding, or entrapment.…”
Section: Introductionmentioning
confidence: 99%
“…pH optrodes usually consist of a pH indicator bound onto a solid support or immobilized in a polymer matrix at the distal end of an optical fiber [7]. Interaction of the indicator at the end of the fiber with the sample leads to changes in Molecules 2020, 25 the optical properties of the indicator which is detected through the optical fiber by absorbance or fluorescence from the sensing material [8,9]. Optrodes have several advantages over glass electrodes including low cost, small size and the robustness of the optical fiber.…”
Section: Introductionmentioning
confidence: 99%